Strategic Alliances in the Asia Pacific: An Overview of Strategic Orientation and Performance in Malaysia - Ghani, Ahmad Bashawir Abdul; Subhan, Muhammad (Universitas Prasetiya Mulya, 2008)
This article presents an overview of the strategic orientation and performance of the cooperative alliances entered into by Malaysian companies in Asia Pacific.. A questionnaire survey to 433 companies was conducted to study the operations of their strategic alliances in Asia Pacific.. A total of 182 companies or 42.0% responded to the survey. It reveals that the companies are mostly local market oriented, and their success is closely associated with three factors; working relationships with partners, difficulties in partnering agreements, and difficulties arising from environment and cultural differences. The three factors above are important regardless of the varying objectives, motives and opinions concerning the benefits and governance of the alliances. In addition to filling a gap in the literature, the study can also serve as a useful reference for Malaysian companies assessing business opportunities in Asia Pacific, which may be actively searching for potential alliance partners and also for foreign companies in seeking business partnership in Malaysia.